Domestic environmental policy under asymmetric information: The role of foreign ownership, outside options and market power - Jon Vislie (University of Oslo, Department of Economics, 2003)
We analyse environmental policy under asymmetric information in a context where a homepolluting firm, selling its final output solely in a foreign market with some market power, has an option to bypass domestic regulation through setting up new plants in a jurisdiction offering lenient environmental standards. The hidden characteristics are emission intensity and outside option, assumed perfectly correlated, so that the firm has a type-dependent reservation utility. There is mixed ownership to the firm; a fraction is owned by foreigners whose welfare does not enter the home government's objective function. The home government has a limited set of policy instruments; in fact only net emissions can be taxed. The familiar trade-off between efficiency and rent extraction will involve over-pollution, with (possibly) a subset of the most emission-intensive firm types being induced to relocate. This effect is reinforced by increased foreign ownership, as the cost of leaving rent then increases. (Ownership has no real impact under complete information.) Weaker market power, due to increased competition at the world market, will work in the same direction, but now there is a counteracting effect due to a lower outside option.
Keywords: D62; D82; H23; L51; Q28; 330; Asymmetric information; environmental regulation; globalisation; Asymmetrische Information; Umweltpolitik; Umweltauflage; Globalisierung